PERANAN AUDIT OPERASIONAL DALAM MENINGKATKAN EFEKTIVITAS PENGELUARAN KAS DI PDAM TIRTA RANDIK SEKAYU KABUPATEN MUSI BANYUASIN - Sunanto Sunanto (Jurnal ACSY : Jurnal Accounting Politeknik Sekayu, 2014)
PDAM Tirta Musi Banyuasin Randik Sekayu is one local manufacturing company and aims to serve the sociaty in MUBA. In this riset, the author examines the company's operational audit activities affect the effectiveness of the company's cash expenditures. Based on the results of a questionnaire distributed directly to the company, the authors conclude that the audit is equally effective and sufficient cash expenditures affect activity, as evidenced by the results of the questionnaire shows the effectiveness rate of 0.73 from the value 1. Companies need to pay attention to the procedures and policies, and internal controls companies such as separation section, functions, and duties of employees in the company. Company should maintain the effectiveness of the company’s, and conduct a thorough examination and further clarify the procedures and internal control company. Keywords: Operational Audit and Effectiveness of Cash Disbushment